Improving Students' Knowledge of The System Development Life Cycle's (SDLC) Implementation Phase Using Gamification (S/O 14515) - Mohamad Hsbollah, Hafizah; Rosli, Khairina (UUM, 2021)
This paper aimed at investigating the use of game-based learning approach in creating meaningful learning experiences and its influence in improving students' knowledge on the subject matter. A total number of 120 students enrolled in the accounting system analysis and design course in a university participated in this experimental study. Grounded by Kolb's experiential learning theory, an experiment was conducted to explore how participants involve themselves in learning from experience by playing educational game. Data were collected through pre and post quiz scores, questionnaire surveys, interviews, and reflections on the students' feedback. The results of the t-test analysis showed that students achieved higher marks after the game intervention and the difference in the mean score between before and after the game played is statistically significant. The findings suggested that the game-based learning approach in teaching and learning can assist students in understanding the subject better than the teacher-centred approach. The results of the study also found that the learning sessions were more engaging and fun as the respondents enjoyed learning through playing games. In addition, the game-based learning approach motivates them to conduct self-study while seeking answers to solve the game tasks. Practically, this study contributes to disseminate awareness among academicians and industry practitioners in developing more educational games that can be used in teaching and learning. Theoretically, it contributes to the existing literature of game-based teaching approach.